THE TRENDS OF HEAT AND MOISTURE SUPPLY INDICATORS IN THE NORTHWESTERN AGRICULTURAL ZONE OF ROSTOV REGION - Marina A. Fomenko; Isida N. Ilyinskaya; Oksana A. Tseluyko; Tatyana A. Oleynikova; Elena A. Babrovskaya (Мелиорация и гидротехника, 2024)
Purpose: to analyze changes in air temperature and precipitation in the northwestern agricultural zone of Rostov region (since there is currently an urgent need to take into account climate changes in a specific soil and climate zone to adjust the composition of crops grown). Continuous operational monitoring of growing conditions for agricultural crops is necessary throughout the growing season. Materials and methods. Synoptic and statistical research methods were used. Results. A trend toward an increase in the average annual air temperature and the sum of temperatures above 10 °C is shown. The warming trend in recent decades in the northwestern zone has become increasingly pronounced, and the annual amount of precipitation has a significant upward trend. Conclusions. During the study period, a trend toward an increase in the average annual temperature and annual precipitation was observed. In general, a comparison of the average annual air temperature for 2000–2023 and 1950–1999 showed an increase from 8.6 to 10.2 °C, or by 18.6 %, while an increase in the average annual precipitation for the study period by 7.5 % was noted. Analysis of the supply curve showed that the probability of exceeding the amount of precipitation of 658 mm is 5 %, 530 mm – 25 %, 458 mm – 50 %, 392 mm – 75 % and 275 mm – 95 %. In general, there is a general trend towards increasing aridization of the climate of the territory, which requires adjustment of breeding work taking into account climate change trends and the implementation of special organizational and economic measures to increase the humidity of the territory due to agro-technical cultivation methods.